DodaLab: an urban health and demographic surveillance site, the first three years in Hanoi, Vietnam. - Tran, T; Eriksson, B; Nguyen, C; Horby, P; Bondjers, G; Petzold, M (2012)
RATIONALE: Health and demographic surveillance sites (HDSSs) are important sources for health planning and policy in many low and middle income countries. Almost all HDSSs are in rural settings. The article aims to present the experiences and some concrete results for the first three years of operation of an urban HDSS in Hanoi, Vietnam, and discuss advantages and disadvantages of conducting health studies in HDSSs. DESIGN, POPULATION AND SAMPLE SIZE: The DodaLab urban HDSS was established in 2007 in three communes at different economic levels in Dong Da district, Hanoi, Vietnam. Demographic, social and economic information about 10,000 households and their 37,000 persons was obtained through household interviews. Quarterly follow-up was initiated to provide information about vital events, birth, death and migration. A new household survey was undertaken in 2009. The existing rural HDSS FilaBavi, started in 1999, with 12,000 households and 52,000 persons, was used as the blueprint. CONCLUSIONS: It was possible to establish and run an urban HDSS with experiences from the rural site. The urban and rural contexts are different and demographically, economically and socially complex, but the use of HDSSs can facilitate research beyond very simplified models for comparisons. General statements about external validity of results from the HDSS cannot be made. This issue has to be considered specifically in every situation as an integral part of the research so that the results can be made useful outside the researched HDSS and in performing relevant comparisons.